STUDY OF THE NEEDS FOR DEVELOPING NEARPOD AS AN INTERACTIVE MULTIMEDIA ON HUMAN RESPIRATORY SYSTEM MATERIAL - Putri Aini, Rabeka; Yuliati, Yuyu; Febriyanto, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of technology in education is increasingly necessary to meet the learning needs of the 21st century. This study aims to identify the need for developing NearPod as interactive multimedia in teaching the human respiratory system to fifth-grade elementary school students. This research uses a quantitative method with a population consisting of teachers and fifth-grade students at SDN Munjul II. The research sample includes 24 teachers and 25 students selected using purposive sampling to ensure proper representation of the target population. Data collection was conducted through media needs questionnaires, interviews, and observations. The results indicate that both teachers and students agree on the importance of developing interactive multimedia to facilitate a more engaging and effective learning process. Most teachers struggle to teach the human respiratory system due to the complexity of the concepts, which are difficult for students to understand. Students face challenges in understanding the material because of the limitations of the available learning media, particularly in visualizing the respiratory process, which cannot be directly observed. This study confirms that the need to develop NearPod is based on the necessity of making the learning process more interactive, with visual elements added to help students grasp abstract concepts.